Hydrogen peroxide in deep waters from the Mediterranean Sea, South Atlantic and South Pacific Oceans - Hopwood, Mark J. (Sci Rep, 2017)
Hydrogen peroxide (H(2)O(2)) is present ubiquitously in marine surface waters where it is a reactive intermediate in the cycling of many trace elements. Photochemical processes are considered the dominant natural H(2)O(2) source, yet cannot explain nanomolar H(2)O(2) concentrations below the photic zone. Here, we determined the concentration of H(2)O(2) in full depth profiles across three ocean basins (Mediterranean Sea, South Atlantic and South Pacific Oceans). To determine the accuracy of H(2)O(2) measurements in the deep ocean we also re-assessed the contribution of interfering species to ‘apparent H(2)O(2)’, as analysed by the luminol based chemiluminescence technique. Within the vicinity of coastal oxygen minimum zones, accurate measurement of H(2)O(2) was not possible due to interference from Fe(II). Offshore, in deep (>1000 m) waters H(2)O(2) concentrations ranged from 0.25 ± 0.27 nM (Mediterranean, Balearics-Algeria) to 2.9 ± 2.2 nM (Mediterranean, Corsica-France). Our results indicate that a dark, pelagic H(2)O(2) production mechanism must occur throughout the deep ocean. A bacterial source of H(2)O(2) is the most likely origin and we show that this source is likely sufficient to account for all of the observed H(2)O(2) in the deep ocean.